The cheese suitability of goat milk when introducing chlorella vulgaris microalgae into their diet - Sufyanova Liliya; Nikolaeva Tatyana; Kislitsyna Nadezhda; Tsaregorodtseva Elena; Shuvalova Elena; Kabanova Tatyana; Ivanov Ivan; Hardina Ekaterina (BIO Web of Conferences, 2024)
Natural milk contains more than 250 components, each of which has a certain importance for human life. The production of cow’s milk has a pronounced seasonal character, when the peak of its production falls in the summer period with a decrease in gross milk yield in winter and spring. In the practice of agricultural enterprises, 60-70% of calving occurs in the spring and summer period. The quality of raw milk has been and remains one of the most relevant topics of cheese making. Fresh natural milk obtained from healthy animals is characterized by certain properties, according to which its suitability for processing is assessed. Changes in the components of milk and its properties also affect its technological properties. The issues of changing the ratio of the main components of goat milk when introducing dry biomass of Chlorella Vulgaris microalgae into the diet are discussed. The characteristic of the milk’s cheese suitability, the yield of cottage cheese, and the correction of the content of heavy metals in cottage cheese are shown.